KESENJANGAN TEKNOLOGI DAN TRANSFORMASI SOSIAL: STUDI PENGARUH AI PADA PENDIDIKAN DI BATAM - Suhartono, Tony (UPPM Sekolah Tinggi Teologi Tabgha Batam, 2025)
This study aims to analyze the impact of inequality in access to technology on student motivation, engagement, and learning outcomes in Batam, as well as explore the influence of artificial intelligence (AI) on their social skills. Inequality of access to technological devices and the internet has the potential to hinder the use of AI in education, worsen academic achievement, and widen the gap in learning and career opportunities in the future. This study uses mixed methods, with quantitative surveys to measure the level of technology access of students, teachers, and parents, as well as qualitative interviews to understand the social and emotional impact of AI use. The results of the study show that students with limited access to technology face obstacles in utilizing digital learning resources, which has an impact on motivation and academic achievement. Although AI is able to improve learning personalization, its use also poses new challenges, such as the decline in direct communication capabilities due to the dominance of digital interactions. Based on these findings, the study recommends strategic measures, such as improving technology infrastructure, device lending programs, and digital skills training for students and teachers. The conclusion of the study emphasizes the need for a balanced approach between technology and social skills development to create an inclusive and equitable learning environment. The implication is that education policies need to support equal access to technology and smart technology integration, so that all students can take optimal advantage of the potential of AI without losing essential social skills in facing the challenges of the modern era